2002
DOI: 10.21273/hortsci.37.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soilless Potting Media and Water Management on Development of Fungus Gnats (Diptera: Sciaridae) and Plant Growth

Abstract: Coconut coir dust is being marketed as a soilless medium substitute for sphagnum peat moss that inhibits fungus gnat (Bradysia sp.) development. However, little information is available on the effects of coconut coir dust on Bradysia sp. In a laboratory study we examined the effect of substituting coconut coir dust for peat moss, with or without a food source, on the development of fungus gnats. An average of less than one adult emerged when 20 fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
(25 reference statements)
3
15
0
5
Order By: Relevance
“…However, the interplay of other factors such as differences in root development, xylem conductance, osmotic adjustment, and stomatal and nonstomatal conductance to CO 2 among species also could have contributed to the lack of differences in A at q levels of 0.15, 0.22, and 0.32 m 3 Ám -3 . Our results are in line with reports available from diverse groups of plants that indicate a threshold level of q for A to decrease and above which no or small differences in A are usually seen (Gindaba et al, 2005;McCree, 1986;Olson et al, 2002;Xu and Zhou, 2005).…”
Section: Resultssupporting
confidence: 93%
“…However, the interplay of other factors such as differences in root development, xylem conductance, osmotic adjustment, and stomatal and nonstomatal conductance to CO 2 among species also could have contributed to the lack of differences in A at q levels of 0.15, 0.22, and 0.32 m 3 Ám -3 . Our results are in line with reports available from diverse groups of plants that indicate a threshold level of q for A to decrease and above which no or small differences in A are usually seen (Gindaba et al, 2005;McCree, 1986;Olson et al, 2002;Xu and Zhou, 2005).…”
Section: Resultssupporting
confidence: 93%
“…coprophila Lintner (Diptera: Sciaridae) adults tended to lay eggs more often in Metro-Mix 560 (The Scott' s Company; Marysville, OH, US) than either Sunshine LC1 Mix (Sungro Horticulture, Inc.; Bellevue, WA, US) or SB300 Universal Professional Growing Mix (Strong-Lite Horticulture Products; Pine Bluff, AK, US) growing media. Fungus gnat adults also appear to be more attracted to or prefer moist growing media containing peat moss (Baker, 1994) since moist growing medium may provide a higher level of fungal activity (Baker, 1994, Olson et al, 2002, which is attractive to and serves as a food source for fungus Effect of growing media and their constituents on fungus gnat, Bradysia sp. nr.…”
Section: Introductionmentioning
confidence: 99%
“…5, fungus gnat adults remained in the central compartment, further validating evidence for repellent activity of the dryer sheets when placed in both sample compartments. Fungus gnat adults are highly attracted to moist growing medium (Baker 1994;Cloyd et al, 2007b;Olson et al, 2002); however, dryer sheet repellency, as demonstrated in Expts. 3 and 5, clearly overcame any attraction to the moist growing medium.…”
Section: Discussionmentioning
confidence: 99%